2017
DOI: 10.1186/s12894-017-0225-3
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative insights into how men with low-risk prostate cancer choosing active surveillance negotiate stress and uncertainty

Abstract: BackgroundActive surveillance is a management strategy for men diagnosed with early-stage, low-risk prostate cancer in which their cancer is monitored and treatment is delayed. This study investigated the primary coping mechanisms for men following the active surveillance treatment plan, with a specific focus on how these men interact with their social network as they negotiate the stress and uncertainty of their diagnosis and treatment approach.MethodsThematic analysis of semi-structured interviews at two aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 30 publications
1
21
1
Order By: Relevance
“…Mishra at al [47] described the views of patients and their families in internet conversations over a 10-year period; they found that access to unbiased information was associated with more patients opting for AS. Four other studies [32, 40, 42, 46] reported similar results. Goh et al [50] found that men who perceived they were receiving consistent information felt more in control of their decision-making and experienced a greater degree of satisfaction and certainty in choosing AS.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Mishra at al [47] described the views of patients and their families in internet conversations over a 10-year period; they found that access to unbiased information was associated with more patients opting for AS. Four other studies [32, 40, 42, 46] reported similar results. Goh et al [50] found that men who perceived they were receiving consistent information felt more in control of their decision-making and experienced a greater degree of satisfaction and certainty in choosing AS.…”
Section: Resultssupporting
confidence: 63%
“…This is important to acknowledge in the context of AS where monitoring includes regular re-biopsy. However, several studies have described the process of repeat testing on AS as a reassuring process [40, 42, 46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the responsibility of the treating physician, not only directed towards the patients but also to their significant others, to facilitate an informed treatment decision. A recently published qualitative study by Mader et al stating that spousal and social support play important roles in helping men understand and accept their PC diagnosis and chosen care plan 24. In our study, 18% of men saw both a urologist and a clinical oncologist but this did not affect the choice of treatment.…”
Section: Discussioncontrasting
confidence: 44%
“…Numerous supportive care interventions are available to help cancer patients or survivors manage common problems such as stress and uncertainty [ 101 , 102 ]. For men with prostate cancer on AS, spousal and social support were important in helping them to cope with their chosen care plan [ 103 ]. Thus, follow-up for AS patients could be improved by assessing QoL, and providing or linking patients experiencing stress related to illness uncertainty with various forms of supportive care.…”
Section: Discussionmentioning
confidence: 99%